The MaCreA Gene Regulates Normal Conidiation and Microcycle Conidiation in Metarhizium acridum - Song, Dongxu; Shi, Youhui; Ji, HengQing; Xia, Yuxian; Peng, Guoxiong (Frontiers in Microbiology, 2019)
As a C2H2 type zinc finger transcription factor, CreA is the key in Carbon Catabolism Repression (CCR) pathway, which negatively regulates the genes in carbon sources utilization. As conidiation in filamentous fungi is affected by nutritional conditions, CreA may contribute to fungal conidiation, which has been well studied in filamentous fungi, especially Aspergillus spp., but researches on entomopathogenic fungi are not enough. In this study, we found a homologous gene MaCreA in Metarhizium acridum, and the MaCreA deletion strain showed delayed conidiation, significant decrease in conidial yield, and 98.88% lower conidial production, when compared with the wild-type strain, and the normal conidiation and microcycle conidiation pattern shift was blocked. RT-qPCR showed that the transcription levels of the genes FlbD and LaeA (related to asexual development) were significantly altered, and those of most of the conidiation-related genes were higher in ΔMaCreA strain. The results of RNA-Seq revealed that MaCreA regulated the two conidiation patterns by mediating genes related to cell cycle, cell division, cell wall, and cell polarity. In conclusion, CreA, as a core regulatory gene in conidiation, provides new insight into the mechanism of conidiation in entomopathogenic fungi.